2012
DOI: 10.1021/es203584d
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Abiotic Reduction of Pesticides in Prairie Pothole Porewaters

Abstract: Prairie pothole lakes (PPLs) are critical hydrological and ecological components of central North America and represent one of the largest inland wetland systems on Earth. These lakes are located within an agricultural region, and many of them are subject to nonpoint-source pesticide pollution. Limited attention, however, has been paid to understanding the impact of PPL water chemistry on the fate and persistence of pesticides. In this study, the abiotic reductive transformation of seven dinitroaniline pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 111 publications
4
62
1
1
Order By: Relevance
“…Abiotic transformation of the antibiotics might contribute a great to the degradation during composting. Research has demonstrated that high-organic soils/sediments tend to produce elevated levels of reduced sulfur compounds (e.g., bisulfide and polysulfides) and iron(II) species, which typically possess strong reducing capacity that may degrade veterinary antibiotics faster than microorganisms (Zeng et al 2011(Zeng et al , 2012Mohatt et al 2011). Similar to the manures, the SAs concentrations in the composts are lower than other TCs and FQs generally; however, SDZ in the soybean meal compost (SMC) and SCX in the rice husk compost (RHC) are prominent due to their significant higher level in the two composts.…”
Section: Veterinary Antibiotic Residues In Compostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic transformation of the antibiotics might contribute a great to the degradation during composting. Research has demonstrated that high-organic soils/sediments tend to produce elevated levels of reduced sulfur compounds (e.g., bisulfide and polysulfides) and iron(II) species, which typically possess strong reducing capacity that may degrade veterinary antibiotics faster than microorganisms (Zeng et al 2011(Zeng et al , 2012Mohatt et al 2011). Similar to the manures, the SAs concentrations in the composts are lower than other TCs and FQs generally; however, SDZ in the soybean meal compost (SMC) and SCX in the rice husk compost (RHC) are prominent due to their significant higher level in the two composts.…”
Section: Veterinary Antibiotic Residues In Compostsmentioning
confidence: 99%
“…Thus, some degradation of antibiotics is likely to occur during the composting, especially during the exothermic stage (Kim et al 2012). Meanwhile, abiotic reaction with reduced sulfur species could remove the antibiotics from the fresh manures during composting (Zeng et al 2011(Zeng et al , 2012. The objectives of the present study were therefore to identify veterinary antibiotic residues in animal manures and different types of compost and to evaluate the ecological risks associated with the application of organic fertilizers in the protected vegetable farming based on the observed concentrations of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…No reduction product of pendimethalin was identified by hexane extraction and GC-MS analysis. Pendimethalin was presumably transformed through reduction of the nitro groups [29,31], which would have produced the more polar and less extractable amino compounds. Extraction using a solvent with a hydrogendonating property may be necessary to recover the amino products.…”
Section: Biochar-mediated Reduction Of Pendimethalin and Trifluralinmentioning
confidence: 99%
“…Finally, biochar may play a role in the natural attenuation of redox-labile contaminants in reducing environments, in a manner similar to other types of BC [23]. Indeed, BC has recently been implicated in the abiotic reduction of pesticides in sediment porewaters in the Prairie Pothole Region [31]. Biochar-mediated reduction of herbicides and explosives Environ.…”
Section: Possible Reaction Mechanisms and Environmental Implication Omentioning
confidence: 99%
“…The behavior of pesticides in soil, therefore, depends on the characteristics and overall function of the ecosystem as well as physicochemical properties of active ingredients and of its formulated products (Flury 1996;Kerle et al 2007). In addition to adsorption and biodegradation, it has been recently shown that reduced sulfur species and dissolved organic matter present in soil/sediment are capable of promoting the in situ transformation of otherwise recalcitrant pesticides (Zeng et al 2011(Zeng et al , 2012.…”
Section: Introductionmentioning
confidence: 99%